Plant hormones and membrane transporters: integrating nutrient uptake, ion homeostasis, and stress responses through hormonal cross-talk - Faizan, Mohammad; Chen, Jingdong; Karabulut, Fadime; Sharma, Renuka; Afzal, Shadma; Sharma, Pooja; Alam, Pravej; Hayat, Shamsul; Khan, Ira; Ahmed, S. Maqbool; Dai, Xigang; Wan, Heping; et al. (Frontiers in Plant Science, 2026)
Plant membrane transporters are essential components in the regulation of nutrient uptake, ion homeostasis, and adaptive responses to environmental stress. These transport processes are tightly coordinated by complex phytohormonal signaling networks. This review provides an in-depth examination of the molecular mechanisms through which major plant hormones including auxins, cytokinins, brassinosteroids, ethylene, abscisic acid, gibberellins, jasmonates, strigolactones, melatonin, karrikins, and gamma-aminobutyric acid (GABA) modulate transporter activity. Each hormone activates distinct signaling pathways that alter the transcription, localization, and functional dynamics of membrane transport proteins, enabling plants to fine-tune physiological responses in accordance with developmental needs and environmental stimuli. Special attention is given to the integration of hormonal signals and how this interplay governs key processes such as stomatal movement, nutrient transport, and hormonal cross-regulation. The review also highlights the role of hormone–transporter crosstalk in optimizing plant performance under both normal growth conditions and various abiotic or biotic stresses. By dissecting these regulatory mechanisms, we offer insights into how phytohormonal control of membrane transport contributes to overall plant fitness. Understanding the coordination between hormonal signaling and transporter networks opens new avenues for crop improvement strategies. Leveraging this knowledge can support the development of resilient plant varieties with enhanced nutrient use efficiency, stress tolerance, and yield potential. This review underscores the significance of transporter–hormone interactions as central elements in plant development and environmental adaptation, positioning them as key targets for future agricultural innovations.